Copeptin and renal function decline, cardiovascular events and mortality in type 1 diabetes. Issue 1 (26th December 2020) - Heinrich, Niels S; Theilade, Simone; Winther, Signe A; Tofte, Nete; Ahluwalia, Tarunveer S; Jeppesen, Jørgen L; Persson, Frederik; Hansen, Tine W; Goetze, Jens P; Rossing, Peter
Abstract: Background: Plasma copeptin is a surrogate of arginine vasopressin (AVP) secretion and is associated with a risk of renal and cardiovascular disease. We investigated associations between copeptin and renal events, cardiovascular events and mortality in type 1 diabetes (T1D). Methods: We conducted a prospective cohort study on 658 individuals with T1D from Steno Diabetes Center Copenhagen. Plasma copeptin concentrations and conventional risk factors were assessed at baseline. The five endpoints were traced through national registries and electronic laboratory records. Results: Baseline mean age was 55 ± 13 years and estimated glomerular filtration rate (eGFR) was 81 ± 26 mL/min/1.73 m 2 . The median follow-up was 6.2 years (interquartile range 5.8–6.7); 123 participants reached a combined renal endpoint [decline in eGFR ≥30%, end-stage kidney disease (ESKD) or all-cause mortality], 93 had a decrease in eGFR ≥30%, 21 developed ESKD, 94 experienced a combined cardiovascular endpoint and 58 died from all causes. Higher copeptin was associated with all endpoints in unadjusted Cox regression analyses. Upon adjustment for baseline eGFR, the associations were attenuated and remained significant only for the combined renal endpoint and decrease in eGFR ≥30%. Results were similar upon further adjustment for other risk factors, after which hazard ratios for the two renal endpoints were 2.27 (95% confidence interval 1.08–4.74) and 4.49 (1.77–11.4), respectively, for the highest versus the lowest quartile of copeptin. Conclusions: Higher copeptin was an independent risk marker for a combined renal endpoint and decline in renal function. AVP may be a marker of renal damage or a factor whose contribution to renal and cardiovascular risk is partially mediated by renal damage.